The destined hour: hostage crisis & a family's ordeal - Rosen, Barbara; Rosen, Barry (Doubleday , N. Y. Garden City, New York, 1982)
Former hostage, Barry Rosen, gives a first-person account of the take-over of the American embassy in Iran and his 444 days in captivity juxtaposed with his wife's account of the effect of these events on the families of the hostages.
Includes Index
Keywords: Rosen, Barry, -- 1944-; Personal narratives -- 1979-1981